The Howiesons Poort of South Africa: what we know, what we think we know, what we need to know - Lombard, M. (Southern African Humanities, 2021)
This contribution aims to provide a concise review of Howiesons Poort research conducted over the past eight decades since the industry was first identified. A review is considered useful in the light of current interest in the industry and what it means in terms of technological and cognitive evolution. It is also true that far-reaching behavioural hypotheses have been built around the Howiesons Poort, some with very little supporting evidence. Recent developments in stone tool analysis, environmental reconstruction and dating methodology are providing us with new tools to measure the time depth and limits of the Howiesons Poort. Such methods may also provide detailed empirical data to build onto or re-assess hypotheses regarding human behaviour associated with this stone tool industry. To cite this article: Lombard, M. 2005. The Howiesons Poort of South Africa: what we know, what we think we know, what we need to know. Southern African Humanities 17: 33-55.